Hambatan Pelaksanaan Putusan Pengadilan oleh Pemerintah - Lamabelawa, Vergilius Septyanto (Penerbit Goodwood, 2025)
Purpose: To explain the obstacles in the implementation of court decisions, as well as to describe the government's non-compliance in executing court rulings from the perspective of the principles of the rule of law and the principles of a democratic state. Methodology/approach: This research uses a normative approach to analyze legal issues related to the implementation of court decisions by the government, utilizing legislative and bibliographic approaches. Results/findings: The implementation of court decisions is based on the good faith of the government. This government action is justified by the principle that the government cannot be declared bankrupt and the principle of contrarius actus. It is also reinforced by regulations in the legislation. Conclutions: The government's liability is a form of repressive legal action to protect society from unlawful acts by the authorities (onrechtmatig overheidsdaad). However, the implementation of court decisions relies on the good faith of the government. The government's disobedience in executing decisions based on its good faith reflects a violation of the principles of the rule of law and democracy, and the government's actions contradict the principles of good governance. Limitations: This research is limited to normative research and is only of a recommendation nature. The implementation is up to the government to carry out. Contribution: Providing understanding in the development of legal science, and hopefully offering benefits for legal practitioners.